PENGARUH PROFITABILITAS, LEVERAGE, INVESTMENT OPPORTUNITY DAN DIVIDEND PAYOUT RATIO TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG LISTED TAHUN 2013-2015 - Ramsiah Ramsiah; M Rasuli; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study is to determine the effect of profitability, leverage (financial risk), investment opportunity, and dividend payout ratio to corporate value. This study uses secondary data r in the form of annual financial statements and annual report (annual report) of manufacturing companies that go public in Indonesia Stock Exchange and the period 2013-2015. The research population is 142 companies, but based on criteria that have only 33 companies that meet the criteria. The sample technique used in this research is purposive sampling method. The method used to analyze the variables in this study using multiple linear regression with the help of SPSS for windows program.Based on the results of research variable independent influence on dependent variable of 24% while the remaining 76% explained by other variables outside the variables used. This means, the independent variable used is not appropriate because it can not explain more than 50% of the dependent variable.Keywords :Profitability, Leverage, Investment Opportunity And Dividend Payout Ratio, Value Of Companies